EFEKTIVITAS PENERAPAN INTAGRATED CLINICAL PATHWAY PADA PENYAKIT PARU: LITERATURE REVIEW - Yuliana, Andi; Rachmawaty, Rini; Saleh, Ariyanti (Universitas Tribhuwana Tunggadewi, 2022)
Globally, lung disease is one of the contributors to the increase in inpatients and the use of health facilities in hospitals. This literature review aims to identify the effectiveness of implementing integrated clinical pathways in lung disease. Methods: The design of this research is a literature review. Search articles using Pubmed, Ebsco, Cochrane Library, and Proquest databases. Structured research questions using the PICO method, and search keywords based on the database in MeSH Term. The inclusion criteria are focused on the application of integrated clinical pathways, applied to health care facilities, applied to lung disease, published in the last 10 years, and in English. There were 3582 articles found, and only 8 articles were included which matched the research question. Results: There were 8 articles included in this study. From the results of a critical assessment of the included articles, the application of ICP in lung disease can reduce patient length of stay, reduce patient care costs, reduce the number of patient readmissions, and reduce drug use in hospitals. Conclusion: The application of ICP in lung disease improves patient outcomes, therefore ICP can be recommended to health care agencies, especially health management.